Negative Effects of Reforming Russian Graduate School: Analysis and Ways to Minimize - M. A. Kashina (Moscow Polytechnic University, 2020)
The transformation of Russian graduate school into the third stage of higher education hasn't increased its effectiveness. The number of theses and graduate students has decreased. The interest of young people in science declines and well as the prestige of scientific activity. Graduate school does not fulfill its primary function as a social institution. It does not ensure the reproduction of research and pedagogical staff in Russia. The purpose of entering graduate school is far from writing a thesis. Hence, the review of the ways and methods of reforming the system of graduate school is necessary. The aim of the study is to analyze the negative consequences of turning graduate school into a higher education level and to develop practical recommendations to minimize these consequences. Research methods: analysis of statistical and sociological data, materials of scientific periodicals, including the articles about preparation of graduate students in other countries. The results of this study. The author structures the factors that generate the above situation and formulates three possible scenarios/alternatives for the development of Russian graduate school, which are "Targeted Support", "Western Model", "One Graduate School - Two Trajectories". The first is formulated as a zero alternative, the "Western Model" - as a radical one. The scenario "One Graduate School - Two Trajectories" is considered as a prior alternative. Perhaps, the scenario will be able to solve the problem of graduate school in current conditions. This alternative suggests that the pedagogical (professional) degree is introduced in addition to the scientific degree in graduate school. Graduate school remains the level of higher education, but at the same time is divided into research branch and pedagogical one. Accordingly, two types of educational programs are required to be created. They should be oriented on different sets of competencies and give different results. This scenario is considered as a temporary measure. It will allow educational institutions of higher education not to lose graduate school as such, especially at those universities where programs of social and humanities branches are implemented. In addition, it will allow to individualize the educational trajectories of graduate students, because it takes into account the capabilities and the inclinations of graduate students. In conclusion, the author presents the practical recommendations that allow this scenario to be implemented.